Problematika Kepemimpinan Komting (Komandan Tingkat) Angkatan 2021 dan 2022 Departemen Ilmu Admnistrasi Negara Universitas Negeri Padang - Syifana Azra; Syamsir Syamsir; Wahyu Shandi Kurniawan (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
Here are lots of problems that occur in the field, such as problems related to the cohesiveness of the members of the Department of State Administration, as well as problems related to programs in the context of organizing the activities of the Department of State Administration, as well as problems regarding class clothes and field work lectures. This condition certainly creates differences of opinion between department members, therefore of the various problems faced by Komting, Komting certainly has strategies and also solutions to these problems. The purpose of this research is to identify the causes or factors of the problems faced by Komting and the strategies implemented by Komting in dealing with the problems that arise. This research was conducted using a qualitative descriptive method. The results of the study say that the first step in solving the problem is solving the problem by looking for causes and not exaggerating the problem and coming must be neutral, see from a different perspective, approach emotionally and question the reasons for the students concerned.